2001
DOI: 10.1002/jcp.10019
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression and activity of four PKC isozymes in confluent and mechanically stimulated UMR‐108 osteoblastic cells

Abstract: The transcript (mRNA), protein levels, enzyme activity, and cellular localization of four protein kinase C (PKC) isozymes identified in rat osteogenic sarcoma cells (UMR-108) were studied at confluent density and during mechanical stress (cyclic stretch). Western blot analysis indicated that growth to confluent density significantly increased the protein levels of cPKC-alpha (11.6-fold), nPKC-delta (5.3-fold), and nPKC-epsilon (22.0-fold) but not aPKC-zeta. Northern blot analysis indicated a significant (2.3-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 41 publications
1
21
0
1
Order By: Relevance
“…In primary rat OBC there is a continuous increase in PKC · expression from early to late cell cultures. Geng et al also demonstrated a marked increase in the level of cPKC-· expression in rat osteogenic sarcoma cells (UMR-108) upon cellular confluency (32).…”
Section: Discussionmentioning
confidence: 93%
“…In primary rat OBC there is a continuous increase in PKC · expression from early to late cell cultures. Geng et al also demonstrated a marked increase in the level of cPKC-· expression in rat osteogenic sarcoma cells (UMR-108) upon cellular confluency (32).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, we observed that rottlerin treatment changed hMSC morphology from its typical spindle-shaped fibroblastic morphology observed in proliferating hMSCs to a triangular shape (Fig. 5C), which is consistent with reports stating that inhibition of PKCδ changes the morphology of hMSCs by altering the cytoskeleton [137,138]. To elucidate which isozyme is involved in this effect, we exposed hMSCs to a PKCθ pseudosubstrate, which inhibits PKCθ activity but does not affect PKCδ activity.…”
Section: Divergent Effects Of Different Pkc Isozyme Inhibitor On Hmscsupporting
confidence: 90%
“…Several PKC isoforms have been reported to act as regulators of cell differentiation, growth, survival, migration, invasion, and apoptosis in various human malignancies (7,10,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Therefore, PKC may be an attractive candidate for targeting using novel anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PKC may be an attractive candidate for targeting using novel anticancer therapies. Among the PKC isoforms, PKCα, β, and γ are the most abundant isoforms in various tissues (19), and in general, PKCα and PKCβ have been linked to increased invasion, proliferation, drug resistance and genetic instability in tumor cells (9,19,21,(24)(25)(26)(27)(28)(29)(30)(31)(32), while PKCδ is thought to promote apoptosis (7,10,33). Koivunen et al theorized that increased proportional activation of PKCα/β to PKCδ is an important factor in the aggressiveness of cancers (9), and other studies demonstrated that PKCβ plays an important role in the signal transduction pathway for vascular endothelial growth factor-mediated tumor development and angiogenesis in human malignancies (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation